UNCTAD Handbook of Statistics 2019 - Conference des Nations Unies sur le commerce et le développement (United Nations, 2019)
This publication was first launched in 1967. Over the past 50 years, the handbook has evolved to incorporate new statistics and ensure that readers have access to the best possible information available. This edition continues in this tradition and introduces 'nowcasted' estimates for total merchandised trade, total services trade and GDP on a worldwide basis.